Evaluation of microbiological processing of urine specimens: comparison of overnight versus two-day incubation. - Murray, P (1992)
In this study the value of urine culture incubation for 1 versus 2 days was determined. The results of the study indicate that 1 day of incubation is reliable if (i) all specimens are incubated for a full 24 h, (ii) all specimens with less than 10(4) uropathogens per ml are incubated for an additional day to ensure accurate quantitation, and (iii) specimens from patients with suspected funguria are incubated for a minimum of 2 days.